The Association Between Physical Activity and Mathematical Achievement Among Chinese Fourth Graders: A Moderated Moderated-Mediation Model - Zhou, Jing; Liu, Hongyun; Wen, Hongbo; Wang, Xiuna; Wang, Yehui; Yang, Tao (Frontiers in Psychology, 2022)
Abstract This study explored the association between out-of-school physical activity (PA) and mathematical achievement in relation to mathematical anxiety (MA), as well as the influence of parents’ support for their children’s physical activity on this association, to examine whether parental support for physical activity affects mental health and academic performance. Data were collected from the responses of 22,509 (52.9% boys) children in Grade 4 from six provinces across eastern, central, and western China who completed the mathematics component and the physical education and health component of the national-level education quality assessment. A moderated moderated-mediation model was tested using PROCESS v3.4 and SPSS v19.0, with socioeconomic status, school location, and body mass index as controlled variables. Out-of-school physical activity had a positive effect on children’s mathematical achievement, and math anxiety partially mediated this association. The indices of conditional moderated mediation through the parental support of both girls and boys were respectively significant, indicating that children can benefit from physical activity, and that increased perceived parental support for physical activity can alleviate their children’s math anxiety and their improve mathematics, regardless of gender. However, gender differences were observed in the influence of parental support for physical activity on anxiety: Although girls’ math anxiety levels were significantly higher, the anxiety levels of girls with high parental support were significantly lower than those of boys with low parental support.